Wissenschaft von der Politik vor der Politikwissenschaft? - König, Thomas; Ehs, Tamara (2012)
Abstract: The academic reform in the 1960s and 1970s were formative years for the history of science in the Second Republic of Austria. Political Science, as a discipline, was particularly affected - not the least because this was the time when the discipline was, finally, institutionalized. This article, however, examines the background why the study of politics and policy in Austria was formalized so late. While often-neglected in the literature, the first two decades academic life of the in the renewed republic are of particular interest to us. What forms of academic (or, scientific) engagement with politics and policy can we find in this pre-discipline era? This question is tackled along three different layers in the contemporary academic framework, firstly epistemological trends, secondly academic practices, and thirdly early forms of institutionalization. The article is part of the ongoing special topic on "40 years of ÖZP" in 2012